Global assessment of the effect of climate change on ammonia emissions from seabirds. (July 2018) - Riddick, Stuart N.; Dragosits, Ulrike; Blackall, Trevor D.; Tomlinson, Sam J.; Daunt, Francis; Wanless, Sarah; Hallsworth, Stephen; Braban, Christine F.; Tang, Y. Sim; Sutton, Mark A.
Abstract: Seabird colonies alter the biogeochemistry of nearby ecosystems, while the associated emissions of ammonia (NH3 ) may cause acidification and eutrophication of finely balanced biomes. To examine the possible effects of future climate change on the magnitude and distribution of seabird NH3 emissions globally, a global seabird database was used as input to the GUANO model, a dynamic mass-flow process-based model that simulates NH3 losses from seabird colonies at an hourly resolution in relation to environmental conditions. Ammonia emissions calculated by the GUANO model were in close agreement with measured NH3 emissions across a wide range of climates. For the year 2010, the total global seabird NH3 emission is estimated at 82 [37–127] Gg year −1 . This is less than previously estimated using a simple temperature-dependent empirical model, mainly due to inclusion of nitrogen wash-off from colonies during precipitation events in the GUANO model. High precipitation, especially between 40° and 60° S, results in total emissions for the penguin species that are 82% smaller than previously estimated, while for species found in dry tropical areas, emissions are 83–133% larger. Application of temperature anomalies for several IPCC scenarios for 2099 in the GUANO model indicated a predicted net increase in global seabird NH3 emissions of 27% (B1 scenario) and 39% (A2 scenario), compared with the 2010 estimates. At individual colonies, the net change was the result of influences of temperature, precipitation and relative humidity change, with smaller effects of wind-speed changes. The largest increases in NH3 emissions (mean: 60% [486 to −50] increase; A2 scenario for 2099 compared with 2010) were found for colonies 40°S to 65°N, and may lead to increased plant growth and decreased biodiversity by eliminating nitrogen sensitive plant species. Only 7% of the seabird colonies assessed globally (mainly limited to the sub-polar Southern Ocean) were estimated to experience a reduction in NH3 emission (average: −18% [-50 to 0] reduction between 2010 and 2099, A2 scenario), where an increase in precipitation was found to more than offset the effect of rising temperatures. Highlights: Magnitude and distribution of seabird NH3 emissions globally calculated by a dynamic mass-flow process-based model. For the year 2010, the total global seabird NH3 emission is estimated at 82 [37–127] Gg year −1 . 2010 estimate is less than previous estimate and 82% smaller for penguin species that breed in high precipitation areas. Using 2099 IPCC scenarios, net increase in global seabird NH3 emissions of 39% (A2 scenario) compared with 2010 estimates.